Do bone grafts or barrier membranes provide additional treatment effects for infrabony lesions treated with enamel matrix derivatives?: A network meta-analysis of randomized-controlled trials - Tu, Yu-Kang; Woolston, Andrew; Faggion Junior, Clóvis Mariano (Journal of clinical periodontology, 2010)
Background/Aim: Network meta-analyses of randomized-controlled trials were undertaken to investigate whether enamel matrix derivatives (EMD) in conjunction with other regenerative materials yield better treatment outcomes than EMD alone in the treatment of infrabony defects ≥3 mm. Material and Methods: A literature search was conducted using the Medline, EMBASE, LILACS and CENTRAL databases up to and including December 2008. Treatment outcomes were changes in probing pocket depth (PPD), clinical attachment level (CAL) and infrabony defect depth. Different types of bone grafts (or barrier membranes) were first treated as a group and then separately. Results: Twenty-eight studies were included in the review. EMD plus bone grafts and EMD plus membranes attained 0.24 mm [95% high probability density (HPD) intervals: −0.38, 0.65] and 0.07 mm (95% HPD intervals: −1.26, 1.04) more PPD reduction than EMD alone, respectively. For CAL gain, EMD plus bone grafts and EMD plus membranes attained 0.46 mm (95% HPD intervals: −0.17, 0.83) and 0.15 mm (95% HPD intervals: −1.37, 0.30), respectively. When different types of bone grafts and barrier membranes were treated separately, EMD with bovine bone grafts showed greater treatment effects. Conclusion: There was little evidence to support the additional benefits of EMD in conjunction with other regenerative materials.
Erstmals am 14 December 2009 online veröffentlicht
Gesehen am 19.01.2024